Evaluación de tres tipos de té de frutas a diferentes frecuencias en el comportamiento agronómico de la asociación de cultivos de lechuga (lactuca sativa), remolacha (beta vulgaris) y apio (apium graveolens) en el Campus Salache, 2023-2024 - Mena Alvarez, Joselyn Aracely (2024)
The present research project was established in order to evaluate fruit tea at diverse frequencies in the agronomic behavior of the association of lettuce (Lactuca sativa), beet (Beta vulgaris) and celery (Apium graveolens) crops at Salache Campus, it is based on the application of fruit tea (P) P1= Papaya, P2= Banana, P3 = Blackberry these were dissolved in 6 liters of water respectively, and in frequencies (F) and on application F1= 15 days, F2= 30 days, F3= 45 days. The variables recorded were: number of leaves, plant height, leaf width, leaf length, number of stems, weight at harvest in the crop associations at 15, 30 and 45 days from the first application. A 3x3 factorial arrangement was applied implementing a completely randomized block design (DBCA) with three repetitions. The obtained results show that according to the plant development, it was identified that the best fruit tea and frequency of application, in the lettuce crop was P2 (Banana) and the frequency F2 (45 days) in the leaf width variable with 13.67 cm, in the weight at harvest with 0.396 kg. In the beet crop, the best tea and frequency was P2 (Banana) and the frequency F2 (45 days) in the variable plant height with 25.67 cm; in the number of leaves with 10.33; in the leaf width with 5.13 cm.; in the leaf length with 12.67 cm.; and weight at harvest with 0.4 kg. In the celery crop, the best tea and frequency was P3 (Blackberry) and the frequency F3 (45 days), in the variable number of stems with 9.33 and in the weight at harvest with 0.25 kg.”